OPTIMIZATION OF CYBER PR AT PRIVATE UNIVERSITIES IN YOGYAKARTA - Mutia Dewi; Sumekar Tanjung; Shalma Nadira (Asian Journal of Innovation and Entrepreneurship, 2019)
This study aims to explain the optimization of cyber PR at private universities in Yogyakarta. High internet penetration in the community forces public relations to utilize communication technology. Thus, this research was conducted at five universities in Yogyakarta based on webometrics rank of 2016/2017 i.e., UII, UMY, UAD, UAJY, and Amikom through observation, interview, and physical and online document search. It is revealed that the public relations in universities not only connect institutions and students or government but also form the universities’ positive image to attract the public's attention. There are eight components played by private universities in their activities: credibility, context, content, clarity, channel, continuity and consistency, capability of the audience, and connectivity. Communication is the most influential key element in cyber-PR activity. Consequently, this should be managed maximally by universities to create a positive image.